eCM 2018
DOI: 10.22203/ecm.v036a08
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells for cartilage repair: current status and future perspectives

Abstract: The establishment of cartilage regenerative medicine is an important clinical issue, but the search for cell sources able to restore cartilage integrity proves to be challenging. Human mesenchymal stromal cells (MSCs) are prone to form epiphyseal or hypertrophic cartilage and have an age-related limited proliferation. On the other hand, it is difficult to obtain functional chondrocytes from human embryonic stem cells (ESCs). Moreover, the ethical issues associated with human ESCs are an additional disadvantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…It has been proposed that these cells are intrinsically committed to bone formation through the endochondral ossification pathway, and that they follow this differentiation program after being exposed to chondrogenic stimuli [111]. However, the lack of reproducibility among chondrogenic protocols is also a feasible explanation [112], and it is important to note that good results have been obtained when performing chondrogenesis onto suitable scaffolds [95]. Finger et al (2003) found that immortalized cell lines obtained from chondrocytes were highly proliferative and showed less expression of genes involved in matrix synthesis and turnover than expected [113], in the same way that higher proliferation rates are related to reduced mineralization upon osteogenic induction [49,110].…”
Section: Chondrogenic Potentialmentioning
confidence: 99%
“…It has been proposed that these cells are intrinsically committed to bone formation through the endochondral ossification pathway, and that they follow this differentiation program after being exposed to chondrogenic stimuli [111]. However, the lack of reproducibility among chondrogenic protocols is also a feasible explanation [112], and it is important to note that good results have been obtained when performing chondrogenesis onto suitable scaffolds [95]. Finger et al (2003) found that immortalized cell lines obtained from chondrocytes were highly proliferative and showed less expression of genes involved in matrix synthesis and turnover than expected [113], in the same way that higher proliferation rates are related to reduced mineralization upon osteogenic induction [49,110].…”
Section: Chondrogenic Potentialmentioning
confidence: 99%
“…of allogeneic or autologous MSCs from pluripotent stem cells has emerged as a promising new strategy for stem cellbased therapy (Yang et al, 2017;Castro-Vinuelas et al, 2018;Soontararak et al, 2018;Yan et al, 2019). In the present study, we have derived MSCs from gene-corrected CS-iPSCs under a cGMP-compliant condition.…”
Section: Research Articlementioning
confidence: 99%
“…Based on previous studies, we have developed a differentiation protocol 37,50 that mimics the development of pluripotent cells through the primitive streak mesendoderm-mesoderm intermediates-chondrocytes pathway. Additionally, the first step of EBs formation supposedly resembles the early post-implantation embryo and the cells in the EB should therefore be able to differentiate into all cell types 7 . Although more research is needed in order to optimise the current protocols for differentiating iPSCs into chondrocytes 7 , here we demonstrate that the iPSC-lines derived from patients with OA of the hand show less capacity to produce extracellular matrix rich in COL and PGs, after the differentiation process, in comparison to the iPSC-line derived from the healthy donor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the first step of EBs formation supposedly resembles the early post-implantation embryo and the cells in the EB should therefore be able to differentiate into all cell types 7 . Although more research is needed in order to optimise the current protocols for differentiating iPSCs into chondrocytes 7 , here we demonstrate that the iPSC-lines derived from patients with OA of the hand show less capacity to produce extracellular matrix rich in COL and PGs, after the differentiation process, in comparison to the iPSC-line derived from the healthy donor. These preliminary results are in accordance with previous studies in which the extracellular matrix of chondrocytes derived from patients' iPSC resembled the one observed during advanced OA 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation